Navigating the supply chain frontier: Insights from SMEs on the effects of inter-organizational collaboration and inter-organizational trust on supply chain performance - George Kankam; Mawuko Dza (Journal of Open Innovation: Technology, Market and Complexity)
This paper explores how inter-organizational trust and inter-organizational collaboration can influence small and medium-sized enterprises (SMEs) supply chain performance. Specifically, the study investigates how inter-organizational collaboration will moderate and mediate inter-organizational trust and supply chain performance. The data were analyzed via confirmatory factor analysis and structural equation modeling (CB-SEM). Data were collected from self-administered questionnaires from 53 managers from 53 manufacturing small and medium-sized enterprises (SMEs). The findings revealed a positive moderation and partial mediating effect of inter-organizational collaboration on trust and supply chain performance. The paper's key practical contribution is that SMEs must work together through effective inter-organization collaboration to build confidence and improve the supply chain network. The contribution of this study centers on the relationship between SMEs through effective open collaboration. The study emphasizes that to foster inter-organizational collaboration SMEs should place premium on open collabrotion, knowledge sharing, leveraging external ideas, open innovation and accesing a pool of talent.